Estabelecimento de uma base de informações para a parte arbitrária da força de interação em uma suspensão particulada - Medeiros, Vanessa Daiany Vieira (2018)
The flow in porous media are relevant in several areas of scientific and technological interest. It is possible to cite a series of unitary operations, interesting to Chemical Process Engineering, involving its application, as in fixed-oil reactors, filtration, drying, chromatography, adsorption, catalytic converters for reduction of automotive pollutants, sedimentation, transport of solids by drag of fluids, among others. The wide application of the flow process in porous media requires, more and more, studies on theoretical formulations, aiming at a more generalized model that contemplates the appearance of new terms in the balance equations such as the power of the interacting forces and thermodynamic couplings, including arbitrary quantities when there is some kind of restriction. In this sense, the theoretical formulation for a porous medium with restriction of incompressibility, modeled by the continuous theory of mixtures without chemical reactions, when applied to the movement of a specialized suspension with restriction of incompatibility, offers of balance equations involving arbitrary quantities, where relations between greatness produce various forms of systems of equations for the suspension movement. Among such magnitudes, the force of arbitrary interaction can be highlighted. In the literature, studies on the arbitrary interaction force in a particulate suspension are still quite scarce. In this work, an expression was obtained for the arbitrary part of the interaction force, as a function only of the porosity variable. It is achieved, on the other hand, on the basis of relations between arbitrary quantities and through the introduction of a new arbitrary function, called a fraction of arbitrary pressures. The establishment of information for the arbitrary part of the interaction force is based on the mathematical modeling of the gravitational movement of a particulate suspension, with incompressibility constraint, in a test tube. The information base and expression for the arbitrary part of the interaction force, presented in this paper, involve basic parameters produced by the modeling, from simple obtaining, which results in an efficient tool for obtaining data and numerical results for the arbitrary part of the interaction force, constituting an important contribution to the study of particulate suspensions with restriction of incompressibility.